Analytical study of some serotonin agonists used in the treatment of migraine - Adel Magdy Awad Michael; Hayam Mahmoud Lotfy; Mamdouh Reda Rezk; Mostafa Abdelaty Shehata (Cairo : Adel Magdy Awad Michael, 2013)
The aim of this work was to develop accurate , precise , sensitive and specific devermination of zolmitriptan and sumatriptan in the pure powder as well as in the pharmaceutical dosage forms . Zolmitriptan was determined by four different techniques . Three stability indicating methods were developed for its determination in the presence of its alkaline and oxidative degradates
Thesis (Ph.D.) - Cairo University - Faculty of Pharmacy - Department of Analytical chemistry
Issued also as CD
Keywords: Spectrophotometry; Sumatriptan; Zolmitriptan